Finding and Bridging Chistian Values: A Conversation Between Christian Missiology and Cultural Identity - Meidy Tatengkeng; Alvyn Hendriks; Stimson Hutagalung; Rolyana Ferinia (JURNAL TERUNA BHAKTI, 2022)
Adventist church does not share any formulation for missiological concept. Its absence leads to Westernization theology where in the systematic theological perspective, Western theology has no interest in accommodating local issues. Consequently, its mission concept presents as a Western formulation with no relevance and significance to the Asian context, specifically Indonesia. This article attempts to construct Indonesian missiological concept that could contribute to evangelism exercise in Central Java. By using qualitative approach, references such as books, articles, and other related sources will receive primary attention. In sum, church mission must find Christian values among the culture and cultural expression should be operated as a medium for evangelism.